Evaluation of the Effectiveness of E-Training in Preparing Scientific Work Using the Kirkpatrick Model - Satyawati, Sophia Tri Satyawati; Marinu Waruwu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Preparing scientific work is a crucial skill, especially for academics, researchers and students. However, not all individuals have access to direct training or have sufficient skills in preparing scientific papers. This research aims to evaluate training programs in developing